Coconutto Essence Enterprise / Mohd Hafizan Harun ... [et al.] - Harun, Mohd Hafizan; Nery, Ben Sakner; Clement, Arona Fiona (2011)
Let us introduce our company, Coconutto Essence Enterprise. Our company is majoring in the fields of manufacturing, specifically, in the producing of the product related to coconut such as the Virgin Coconut Oil (VCO) and coconut-based healthcare product. Coconut as we know is found across much of the tropics, the coconut is known for its great versatility as seen in the many domestic, commercial. and industrial uses of its different parts. Coconuts are part of the daily diet of many people. Its endosperm is known as the edible "meat" of the coconut; when dried it is called copra. The oil and milk derived from it are commonly used in cooking and frying; coconut oil is also widely used in soaps and cosmetics. The clear liquid coconut water within is a refreshing drink and can be processed to create alcohol. The husks and leaves can be used as material to make a variety of products for furnishing and decorating. It also has cultural and religjous significance in many societies that use it.